The conflict of values in the context of acceptance of multiculturalism - Mamzer, Hanna (Kultura-Społeczeństwo-Edukacja, 2019)
There is a quite big progress in the area of education on acceptance and tolerance towards multiculturalism. The main supporter of politics of multiculturalism is Will Kymlicka, and therefore I refer to his thoughts in this essay. However, in contemporary socio-cultural situation of Western civilization, we need something more than the mere acceptance of cultural diversity. It is worth promoting educational programmes that include themes related to the raising of citizens’ awareness of boundaries of self – both in the individual and group aspect. At the same time majority groups should be supported by some tools that would help them to protect their identities without harming others.